The Not-So-Easy Road of Overseas Study: Life like an Outsider - Palmer, Yolanda (Journal of International Students, 2015)
Contemplating my graduate student experience overseas, I constantly viewed myself as an isolate, one who did not belong in the new community of practice. I encountered numerous lingua-cultural, academic and social challenges which led to my lack of community and belonging. This paper is a reflection of my experiences as an international graduate student in a Canadian university. Through this reflection, I explore some of my most potent experiences and how these influenced me as I sojourned through the not-so-easy road of study overseas. This paper also describes the processes I used that enabled me to successfully maneuver and negotiate my journey on the not-so easy-road of studying in a post-secondary institution overseas.